2020
DOI: 10.21203/rs.3.rs-90203/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ENT Manifestations in COVID-19 Positive Patients

Abstract: AIM: To study the status of ear, nose and throat in the patients diagnosed with the CoViD-19.MATERIAL AND METHODS: This is a perspective study in patients admitted in the isolation wards of Dr. Sushila Tiwari Hospital Haldwani between March 2020 and July 2020. There were 465 symptomatic patients out of total 727 patients diagnosed with CoViD-19 .RESULT: Since the CoViD-19 pandemic has begun, many individuals have noted many ENT manifestations along with the other general symptoms like fever(395 pt)>cough (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…These 40 studies (reporting on 43 cohorts) were subjected to a meta-analysis (Table ). Fifteen studies reported anosmia prevalence in 18 cohorts with a total of 7247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait or Singapore and 12 from India or Pakistan. We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table , illustrated in Figure A and B). , The differences in results between the two types of cohorts are shown in the forest plots (Figure A). The pooled prevalence of olfactory dysfunction in the same ethnicity (South Asians) in regions with D614 predominance was 5.33% (95% confidence interval, CI = 3.52–8.00%), while in regions with G614 predominance, it was 31.79% (95% CI = 23.26–41.76%) (Figure A, C).…”
Section: Resultsmentioning
confidence: 99%
“…These 40 studies (reporting on 43 cohorts) were subjected to a meta-analysis (Table ). Fifteen studies reported anosmia prevalence in 18 cohorts with a total of 7247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait or Singapore and 12 from India or Pakistan. We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table , illustrated in Figure A and B). , The differences in results between the two types of cohorts are shown in the forest plots (Figure A). The pooled prevalence of olfactory dysfunction in the same ethnicity (South Asians) in regions with D614 predominance was 5.33% (95% confidence interval, CI = 3.52–8.00%), while in regions with G614 predominance, it was 31.79% (95% CI = 23.26–41.76%) (Figure A, C).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a hospital-based study conducted to assess ENT manifestations among 465 symptomatic COVID patients admitted in an isolated ward of Haldwani (Uttarkhand) by Kuchhal V et al, it was noted that loss of smell (88), nasal congestion (72) and nasal blockade (66) were the common nasal symptoms. Itching in the ear (37), fullness in the ear (20), conduction hearing loss (12) and earache (10) were the most common ear manifestations; whereas dry cough (319), loss of taste (74) and cough with sputum (7) were the most common throat manifestations [6]. In on our study, the order of frequency of taste disturbance for basic four taste were loss of salt taste 81.8%, followed by loss of sweet taste 81.5%, loss of sour taste 60.4% and loss of bitter taste 57.5%.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that most significant predictive ENT symptoms were cough, loss of smell sensation, and sore throat [7]. In the study done by Chaurasia et al, throat symptoms were found to be the most common symptoms including taste dysfunction in 74 patients out of 465 patients [8]. Systematic review conducted by Joanna Krajewska1 et al found that the most prevalent ENT symptoms seen in patients with SARS-CoV-2 were dry cough, sore throat and breathing difficulty [9].…”
Section: Discussionmentioning
confidence: 99%